Niacin attenuates lung inflammation and improves survival during sepsis by downregulating the nuclear factor-κB pathway - Kwon, Woon Yong; Suh, Gil Joon; Kim, Kyung Su; Kwak, Young Ho (Critical care medicine, 2011)
To examine whether niacin attenuates lung inflammation and improves survival during sepsis and to determine whether the beneficial effects of niacin are associated with downregulation of the nuclear factor (NF)-κB pathway. Prospective laboratory study. University laboratory. Male Sprague-Dawley rats (n = 119). To induce endotoxemia in rats, lipopolysaccharide (Escherichia coli, O26:B6) at a dosage of 10 mg/kg was injected into a tail vein and 10 mins later, vehicle, a low dose of niacin (360 mg/kg), or a high dose of niacin (1180 mg/kg) was administered once through an orogastric tube, respectively. We observed the survival of the subjects for 72 hrs. At 6 hrs postlipopolysaccharide, we euthanized animals and measured cytoplasmic phosphorylated inhibitor κB-α and inhibitor κB-α expressions, nuclear NF-κB p65 expression, NF-κB p65 DNA-binding activity, tumor necrosis factor-α, and interleukin-6 gene expressions and histologic damages in lung tissues. We also measured nicotinamide adenine dinucleotide, reduced nicotinamide adenine dinucleotide phosphate, reduced glutathione, and malondialdehyde levels in lung tissues. High dose of niacin suppressed NF-κB activation and proinflammatory cytokine gene expressions in lung tissues, reduced histologic lung damages, and improved survival in endotoxemic rats. Furthermore, it increased nicotinamide adenine dinucleotide, nicotinamide adenine dinucleotide phosphate, and glutathione levels and decreased malondialdehyde level in lung tissues. High dose of niacin attenuated lung inflammation, reduced histologic lung damages, and improved survival during sepsis in rats. These therapeutic benefits were associated with downregulation of the NF-κB pathway.